2003
DOI: 10.1007/s10350-004-6658-2
|View full text |Cite
|
Sign up to set email alerts
|

Cyclooxygenase-2 Expression in Colorectal Adenomas

Abstract: Observed associations suggest that cyclooxygenase-2 plays an important role in progression of the adenoma-to-carcinoma sequence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
18
0
1

Year Published

2003
2003
2006
2006

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 24 publications
2
18
0
1
Order By: Relevance
“…There are suggestions that advanced adenomas have more genetic changes than the earlier lesions, but differences in the expression and mutation status of p53, bcl-2, K-ras, and others have also been inconsistent (66)(67)(68). Cyclooxygenase-2 expression may be another relevant difference between early and more advanced adenomas, as it seems more extensive in large and villous polyps (69)(70)(71), and levels of cyclooxygenase-2 protein increase with degree of dysplasia (69,72,73). These factors could explain a greater sensitivity of advanced adenomas to aspirin and/or calcium, but they do not explain a positive interaction between the two factors specifically for advanced lesions, and we cannot give a convincing explanation for the differences seen in our findings for advanced and nonadvanced adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…There are suggestions that advanced adenomas have more genetic changes than the earlier lesions, but differences in the expression and mutation status of p53, bcl-2, K-ras, and others have also been inconsistent (66)(67)(68). Cyclooxygenase-2 expression may be another relevant difference between early and more advanced adenomas, as it seems more extensive in large and villous polyps (69)(70)(71), and levels of cyclooxygenase-2 protein increase with degree of dysplasia (69,72,73). These factors could explain a greater sensitivity of advanced adenomas to aspirin and/or calcium, but they do not explain a positive interaction between the two factors specifically for advanced lesions, and we cannot give a convincing explanation for the differences seen in our findings for advanced and nonadvanced adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, there was a clear separation from the minimal COX-2 expression by normal large bowel epithelium, and the progressively increasing amount was expressed depending on the degree of dysplasia and advancement from histology of early juvenile/hyperplastic polyp to adenomatous to serrated histology. In a study of sporadic adenomas, it was found that the degree of COX-2 expression related to their increasing size, degree of dysplasia, and, in one study, colonic site (distal rather than proximal) (18,19). We did not have enough recently removed HMPS polyps to try and correlate polyp size and site to COX-2 expression.…”
Section: Discussionmentioning
confidence: 97%
“…The nature of these mononuclear stromal COX-2-expressing cells and their role in promoting or suppressing the pathway to neoplasia in HMPS remain to be elucidated (23)(24)(25). These COX-2 containing tumor stromal cells have included those described as myofibroblasts (22), fibroblasts (5,8), and macrophages (15,18,20,21).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…8,9 COX-2 expression is increased in colorectal adenoma compared with normal mucosa [10][11][12] and the intensity of the expression correlates with the size of adenoma 13 and grade of dysplasia. 14 These observations indicate that COX-2 plays an important role in colorectal carcinogenesis.…”
mentioning
confidence: 96%